Lingkungan Kerja, Motivasi dan Kinerja Karyawan CV. Sari Bhuana Cash & Credit - I Kadek Rika Siswantara; Komang Krisna Heryanda (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of (1) work environment on employee performance, (2) work motivation on employee performance, (3) work environment on motivation, (4) work environment on employee performance through motivation on CV. Sari Bhuana Cash & Credit Singaraja Branch. The research design used in this study were causal quantitative. The object of this study focuses on variables work environment, motivation and employee performance. The subjects of this study were all employees on the CV. Sari Bhuana Cash & Credit Singaraja Branch with a population of 152 people. Data collected by questionnaire and analyzed by path analysis. The results obtained in this study indicate that, (1) the work environment has a positive and significant effect on employee performance, (2) motivation has a positive and significant effect on employee performance, (3) the work environment has a positive and significant effect on motivation, (4 ) the work environment has a positive and significant effect on employee performance through motivation on CV. Sari Bhuana Cash & Credit Singaraja Branch.